ORGANOLEPTIC TEST OF FRESH PINEAPPLE FRUIT JUICE (Ananas Comosus (L.) Merr.) FROM KOTAMOBAGU AND BITUNG CITY - Frandi Mangindano (UNIVERSITAS SAM RATULANGI, 2023)
Pineapple (Ananas comosus (L.) Merr.) is one of the most widely cultivated fruit plants in Indonesia. This plant has many benefits, especially the fruit itself. This study aims to compare the color, aroma, taste, and texture of pineapple juice from Kotamobagu City and Bitung City. The research method used is hedonic by testing the organoleptic test of each sample on 4 parameters. From the results of this study, it can be seen that fresh pineapple juice from Kotamobagu and Kota bitung, which is dissolved in distilled water, each has a distinctive value of four (4) parameters (Color, Taste, Aroma, and Texture). Excellent/preferred scores were found in sample A (fresh pineapple from Kotamobagu).